Women's Responses towards Female Nudity in Advertising - Surendranath, Anupama (2012)
Female nudity has been explicitly used in advertisements. They have been around for a while and continue to be a significant part of the promotion technique. Consumers have different opinions about these advertisements. This study focuses on women’s responses towards female nudity in advertising. A comprehensive review on previous literature emphasis the different roles portrayed by women, memorization, brand recall, arousal and attraction, positive impacts, negative impacts, purchase intention, and cultural studies. The qualitative interviews serve in accumulating dynamic information from respondents. Semi-structure interviews were conducted with women for their thoughts, perceptions and interpretations towards female nudity in two print advertisements. The analysis revealed their attitude, impacts and influence of these advertisements.